Sykepleierstudenters erfaring med relevansen av vitenskapsteori i praksisstudiene - Pedersen, Karen Louise; Einarsen, Kari Anne (Nordisk Tidsskrift for Helseforskning, 2013)
AbstractNursing students’ experiences of the relevance of the theory of science in clinical practiceThis article presents nursing students’ experiences of the relevance of the theory of science in clinical practice. These experiences come to light in focus group interviews with third-year students. The results show that students may perceive the theory of science as vague and meaningless, while at the same time it gives them a perspective on the nursing profession and provides an opportunity to view their own practice from a critical perspective. However, the theory of science becomes more comprehensible through metaphor, more meaningful through narratives, and more concrete via nursing theories. When the students describe their experiences of the relevance of the theory of science, these descriptions are often related to their own life-world and their view of humanity.The students would nevertheless like an opportunity to discuss the theory of science related to situations in clinical practice. They also accept that they are required to be theoretically prepared. The article concludes that the goal of such discussions, where the students share experiences related to the theory of science, is the process of gaining insight, not coming up with the “right” answers.